Knowledge of private dentists in district 5 Manila about biologic width in human periodontium and its significance in restorative dentistry - Bojare, Estrella Marie B.; De Leon, Estrella Marie B. (Department of Community Dentistry, University of the Philippines Manila, 2016)
INTRODUCTION: Biologic width is an important physiologic dimension that has been well-documented in literature. Research studies have been consistent about factors that can potentially violate this important anatomic space. Utmost emphasis was given on the importance of margin placements of crowns and other restorative treatments and yet, violations to the biologic width are still often committed by general practitioners. Thus, this study attempts to gauge and assess the knowledge and understanding of dentists regarding biologic width in general, and specifically its significance, preservation and the consequences once iatrogenic violations have been done